S stelmaria7 New member Joined Mar 2, 2011 Messages 1 Mar 2, 2011 #1 I'm given the equation m=6; (2,2) m being the slope. So I got y-2=6(x-2) y-2=6x-12 y=6x-10 but then i'm just stuck. How do I change y=6X-10 into Ax+By=C?

I'm given the equation m=6; (2,2) m being the slope. So I got y-2=6(x-2) y-2=6x-12 y=6x-10 but then i'm just stuck. How do I change y=6X-10 into Ax+By=C?

S Subhotosh Khan Super Moderator Staff member Joined Jun 18, 2007 Messages 18,133 Mar 2, 2011 #2 stelmaria7 said: I'm given the equation m=6; (2,2) m being the slope. So I got y-2=6(x-2) y-2=6x-12 y=6x-10 but then i'm just stuck. How do I change y=6X-10 into Ax+By=C? Click to expand... 6x - y = 10

stelmaria7 said: I'm given the equation m=6; (2,2) m being the slope. So I got y-2=6(x-2) y-2=6x-12 y=6x-10 but then i'm just stuck. How do I change y=6X-10 into Ax+By=C? Click to expand... 6x - y = 10